2011
DOI: 10.1074/jbc.m111.256974
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Signal Perception and Integration by the Innate Immune Sensor Retinoic Acid-inducible Gene-I (RIG-I)

Abstract: RIG-I is a major innate immune sensor for viral infection, triggering an interferon (IFN)-mediated antiviral response upon cytosolic detection of viral RNA. Double-strandedness and 5-terminal triphosphates were identified as motifs required to elicit optimal immunological signaling. However, very little is known about the response dynamics of the RIG-I pathway, which is crucial for the ability of the cell to react to diverse classes of viral RNA while maintaining self-tolerance. In the present study, we addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
126
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(138 citation statements)
references
References 36 publications
7
126
1
1
Order By: Relevance
“…Indeed, RNase footprinting of RIG-I/dsRNA complexes showed that the minimum length of RNA protected by RIG-I is 10-15 bp, consistent with both the cocrystal structures and the functional titration and microscopy experiments (Binder et al 2011). Multiple copies of RIG-I can thus bind to dsRNA depending on its length.…”
Section: Rig-i Multimerization and Signalingsupporting
confidence: 48%
See 2 more Smart Citations
“…Indeed, RNase footprinting of RIG-I/dsRNA complexes showed that the minimum length of RNA protected by RIG-I is 10-15 bp, consistent with both the cocrystal structures and the functional titration and microscopy experiments (Binder et al 2011). Multiple copies of RIG-I can thus bind to dsRNA depending on its length.…”
Section: Rig-i Multimerization and Signalingsupporting
confidence: 48%
“…This suggests that the higher affinity and significantly longer off-rate of 59ppp bpRNA to the CTD, as compared with 59OH bpRNA or 59p bpRNA (Lu et al 2010;Wang et al 2010), is sufficient to discriminate active and inactive ligands. It has also been reported that much longer dsRNAs (>200 bp), including poly(I:C), not necessarily bearing a 59ppp-end or even being blunt-ended, can also induce IFN via RIG-I (Strahle et al 2007;Kato et al 2008;Binder et al 2011). This is more difficult to explain from a structural and biochemical point of view because of the much lower intrinsic affinity of RIG-I for such RNAs.…”
Section: Dsrna and Its 59ppp-ends As Viral Pampsmentioning
confidence: 73%
See 1 more Smart Citation
“…Binder et al [27] showed some evidence of RIG-I oligomerization on dsRNA by scanning force microscopy and size-exclusion chromatography. However, the role of 5 0 -ppp on RNA was not tested and the experiments were performed in the absence of ATP, which is an essential co-factor for activation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that MDA5 (and RIG-I) forms a higher-order structure during viral RNA recognition for efficient antiviral signaling (14)(15)(16). Receptor oligomerization or clustering, as demonstrated in other receptors, such as inflammasomes, Toll-like receptors, T-and B-cell receptors, is often important for ligand sensitivity and downstream signaling efficiency (17,18).…”
mentioning
confidence: 99%